Molecular detection of rifampicin-resistant Mycobacterium tuberculosis by polymerase chain reaction in Ethiopia: a systematic review and meta-analysis - Birhanu, Molla Yigzaw; Bekele, Getamesay Molla; Jemberie, Selamawit Shita (Frontiers in Medicine, 2024)
Tuberculosis is a contagious bacterial disease caused by Mycobacterium tuberculosis. The emergence and spread of drug-resistant strains of M. tuberculosis in both developing and developed countries has made diagnosis, treatment, and control of tuberculosis more difficult. The PCR assay, which is a fast and sensitive technique and an alternative method for detecting multidrug-resistant tuberculosis, is used to determine RIF resistantresistance. There is no single figure in Ethiopia that represents rifampicin -resistant tuberculosis that is why this study was conducted to overcome the inconsistency the results of the prior studies.Studies were researched from five major electronic databases. The data was extracted using Microsoft Excel, and the data were managed and analyzed using Stata TM Version 17.0 statistical software. The Forest plots was used to check the presence of heterogeneity. The publication bias, meta-regression, and subgroup analysis were used to find out the source of heterogeneity. A random effect analysis model was used to pool the prevalence of RR TB from primary studies and associated factors of RR among TB patients was were identified using meta Meta regression. The presence of association was reported using OR with 95% CI.The overall pooled prevalence of tuberculosis was 14.9% (95% CI: 13.34, 16.46), of these about 7.48% (95% CI: 6.30, 8.66) showeding Rifampicin resistant tuberculosis in Ethiopia. Among the computed variables, living with HIV1.39 (95%CI: 1.13, 1.72) and having a history of TB treatment were 2.05 (95%CI: 1.34, 3.15) were identified as significant factors associated with RR TB in Ethiopia.Drug-resistant TB was is one of the prevalent emerging infectious diseases among TB patients, which affects about one out of every thirteen TB patients. Having TB-HIV coinfection and a history of prior TB treatment were identified as significant factors associated with RR TB.To prevent and control RR TB, patients should complete their follow-up course; the health professionals should educate the actions taken by the patients when they experience drug toxicity and side effects; and the minister Minister of Health should initiate telemedicine, and recruit tracers Formatted: Font: Italic to overcome TB patients' default and to have good drug adherence and retention after initiation of the treatment.